Method for accelerating aging of micro-plastics by in-situ production of hydrogen peroxide from phenolic wastewater

By using phenol in phenol wastewater as an electron donor in water, combined with C3N4 photocatalyst, H2O2 is generated in situ, synergistic degradation of phenol wastewater and microplastics is achieved, the problem of composite pollution in water is solved, and efficient and environmentally friendly purification effect is achieved.

CN119771476AInactive Publication Date: 2025-04-08HENAN NORMAL UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510273737.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-10
Publication Date
2025-04-08
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to effectively solve the problem of the coexistence of phenolic wastewater and microplastics in water bodies, and the method of using photocatalytic production of H2O2 requires additional organic solvents, which increases the pollution load and treatment cost.

Method used

By using phenol in phenol wastewater as an electron donor, combined with the secondary thermally stripped C3N4 photocatalyst, H2O2 is generated in situ, achieving synergistic photocatalytic degradation of phenolic pollutants and plastic films.

Benefits of technology

This method does not require additional organic matter, and uses pollutants to degrade themselves to generate H2O2, which realizes efficient aging of microplastics and degradation of phenolic wastewater, reduces energy consumption and pollution load, and provides a green and low-energy purification method.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119771476A_ABST
    Figure CN119771476A_ABST
Patent Text Reader

Abstract

The invention discloses a method for accelerating aging of micro-plastics by in-situ production of hydrogen peroxide from phenolic wastewater, which comprises the following steps: adding a C3N4 photocatalyst subjected to secondary thermal stripping into to-be-treated wastewater containing both phenolic wastewater and micro-plastics to form a photocatalytic system, and realizing synergistic photocatalytic degradation of phenolic wastewater and micro-plastics under illumination. The C3N4 photocatalyst is prepared by synthesizing large carbon nitride CN through thermal decomposition of dicyandiamide and then carrying out secondary calcination on carbon nitride. According to the method, on the premise of not additionally increasing the water treatment cost, H2O2 is generated in situ to accelerate the aging of the microplastics through the synergistic coupling of the phenol pollutants and the C3N4 photocatalyst in the water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of microplastic aging technology and water pollution control, and in particular to a method for accelerating microplastic aging by in-situ production of hydrogen peroxide using phenolic wastewater. Background Art

[0002] With the development of society and the acceleration of industrialization, various organic and inorganic pollutants coexist in water bodies, making wastewater treatment more difficult and complicated. For example, plastics are widely used in industries such as packaging, construction, automobiles and electronics. Up to 79% of plastic products are discarded into the environment and flow into water bodies after use, coexisting with other organic pollutants. In addition, plastics in the environment may be affected by natural processes such as ultraviolet radiation, mechanical wear, hydrolysis and biodegradation during migration, resulting in aging, and aged plastics are more likely to adsorb pollutants in the environment (such as organic matter, heavy metals, etc.). This leads to the widespread existence of plastics and organic pollutants in natural water bodies and sediments. The coexistence and interaction of multiple pollutants make environmental remediation more difficult and complicated. Studies have shown that increasing the concentration of H2O2 accelerates the aging of microplastics, resulting in significant changes in the color, surface, particle size, hydrophilicity, crystallinity and other aspects of microplastics. As a green oxidant, H2O2 plays a vital role in environmental remediation and is a precursor to the generation of •OH. The strong oxidizing property of •OH can oxidize and decompose toxic organic pollutants into relatively small harmful substances until the final products are CO2 and H2O. However, these studies on the in-situ production of H2O2 using photocatalytic photogenerated electrons often require the addition of alcohols for photogenerated hole reactions, improve charge separation, and provide protons for photocatalytic reactions. However, after the introduction of organic solvents in the reaction system, purification is required in further applications, which increases the pollution load and treatment costs.

[0003] Phenol is an important phenol derivative and is widely used in many fields. In industrial production processes, organic materials such as phenol are often used as raw materials. However, these processes inevitably cause evaporation, leakage, overuse, and organic residue pollution. Phenol is a common organic pollutant in the environment, and previous studies have focused on the degradation and removal of phenol. However, the role of phenol in water purification is often overlooked. The molecular structure of phenol is an ideal electron donor and can be used as a hole scavenger to replace additional alcohol addition. In situ use of pollutants in wastewater to produce H2O2 with strong oxidizing ability, thereby further oxidizing other pollutants in the coexistence system, and achieving waste treatment. Although there are currently reported methods for degrading microplastics or phenolic wastewater alone, no method has been found to use organic matter in wastewater to produce H2O2 in situ to promote microplastic aging. Therefore, the present invention aims to accelerate the aging of microplastics by in-situ production of hydrogen peroxide from phenolic wastewater, providing a green and low-energy purification method for solving the problem of coexistence of pollutants in the natural environment. Summary of the invention

[0004] In view of the problem of complex water pollution caused by the large-scale use of existing phenolic wastewater and microplastics, the present invention provides a method for accelerating the aging of microplastics by in-situ production of hydrogen peroxide using phenolic wastewater. The method provided by the present invention effectively degrades phenolic wastewater of different concentrations by photocatalytic technology while accelerating the aging of plastics, providing a new solution to the complex pollution of coexistence of phenolic wastewater and microplastics in water bodies.

[0005] To achieve the above object, the present invention provides the following technical solutions: A secondary thermally stripped C3N4 photocatalyst is prepared by synthesizing bulk carbon nitride CN by thermally decomposing dicyandiamide and then performing secondary calcination on the carbon nitride.

[0006] Furthermore, the specific preparation method of the C3N4 photocatalyst is as follows: dicyandiamide is placed in a semi-closed quartz boat in a static air environment, and then calcined in a muffle furnace at 550°C for 4 h; next, the calcined material is ground into powder, rinsed with anhydrous ethanol and deionized water, collected by centrifugation, and dried in an oven at 60°C for 12 h; then CN is dispersed in an open quartz boat and calcined in a muffle furnace at 500°C for 4 h to obtain the final material named CN-T, that is, the secondary thermally stripped C3N4 photocatalyst.

[0007] The present invention provides a method for accelerating the aging of microplastics by in-situ production of hydrogen peroxide in phenolic wastewater. In the wastewater to be treated in which phenolic pollutants and plastic films coexist, the above-mentioned secondary thermally stripped C3N4 photocatalyst is added to form a photocatalytic degradation system, and H2O2 is generated in-situ under light to achieve synergistic photocatalytic degradation of phenolic pollutants and plastic films.

[0008] Furthermore, in the photocatalytic degradation system, the addition amount of the secondary thermally stripped C3N4 photocatalyst CN-T is 0.5 g / L, the concentration of the phenolic pollutants is 0-40 mg / L, and no pH adjustment is required.

[0009] Furthermore, the phenolic pollutant is phenol, and the plastic film is a polyethylene plastic film.

[0010] Furthermore, the method is specifically carried out as follows: the concentration of phenolic pollutants in the wastewater to be treated containing plastic film is determined, and the concentration is regulated by diluting or adding phenolic pollutants; during the plastic aging process, a phenol solution of the initial concentration is added to the beaker every 3 hours until the reaction is completed, so that the concentration of phenolic wastewater is maintained at 10-40 mg / L; CN-T photocatalyst is added to the simulated wastewater to be treated in an amount of 0.5 g / L to form a C3N4 / LED photocatalytic degradation system; finally, magnetic stirring is performed at 500 rpm for 30 min in dark conditions, and then the photocatalytic degradation reaction is carried out under LED light for 12-48 hours, thereby completing the synergistic photocatalytic degradation of phenolic pollutants and plastic film.

[0011] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention utilizes phenol as an electron donor to enhance the production of H2O2 without the need to add additional exogenous organic matter, and phenol itself can be degraded, providing a new energy-saving and environmentally friendly method for oxidizing coexisting pollutants by utilizing active species with strong oxidizing ability generated during the degradation of pollutants.

[0012] (2) The present invention is based on the strong electron-donating properties of the hydroxyl group on the aromatic ring of phenol, which is easily + A thermally stripped C3N4 material rich in aromatic carbon was developed. This material effectively promotes the photogenerated electrons to participate in the two-electron reduction process of dissolved oxygen to generate H2O2 through the π-π interaction with phenol, thereby achieving efficient oxidation of coexisting pollutants. In the process of photocatalytic degradation, phenol can be adsorbed onto the surface of the photocatalyst through the π-π interaction between the benzene ring and the triazine ring, forming surface-adsorbed phenol* and photoactivated h + It can directly oxidize phenol*, thereby reducing the recombination rate of electrons and holes and releasing more e - Reduction with O2 generates H2O2 in situ. The generated H2O2 and •OH degrade the weak links (such as chromophores and defects) of the long polymer chain to generate low molecular weight polyethylene alkyl, which then undergoes chain scission, branching, cross-linking and microplastic oxidation.

[0013] (3) The present invention utilizes phenol degradation to generate H2O2 in situ, and the H2O2 production increases with the increase of phenol concentration in the initial solution. When phenol is completely degraded, the H2O2 production decreases, and the aging degree of PE plastic becomes more obvious with the increase of phenol concentration. The oxygen content and roughness of the surface of PE plastic also increase significantly, changing from hydrophobic to hydrophilic, and the agglomeration effect is enhanced, which is beneficial to the subsequent separation and recycling.

[0014] (4) This study elucidates the key role of phenol addition in dual pollutant removal, which is of great significance for understanding the role of phenol in the natural environment and the fate of coexisting pollutants. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 is a comparison chart of H2O2 production in deionized water and phenol of different concentrations in Example 1 of the present invention; Figure 2 Graph (a) of photocatalytic degradation of phenol at different concentrations and graph (b) of in-situ production of H2O2 in Example 1 of the present invention; Figure 3 is an infrared spectrum of PE plastic in Example 2 of the present invention reacted in deionized water and phenol wastewater for 48 hours; Figure 4 The infrared spectra of PE plastics reacted with phenol wastewater of different concentrations for 48 h in Example 2 of the present invention (a) and the maximum amount of •OH generated in the system (b); Figure 5 It is the infrared spectra of the PE plastic in Example 3 of the present invention reacting in phenol wastewater (40 mg / L) at different reaction times. DETAILED DESCRIPTION

[0016] The following is a detailed description of an embodiment of the present invention. This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiment.

[0017] The apparatus used in the following examples mainly consists of a 100 mL beaker, a magnetic stirrer, and a 21 W LED lamp (with a maximum emission peak of 416 nm).

[0018] Preparation of the secondary thermally exfoliated C3N4 photocatalyst (CN-T photocatalyst): Dicyandiamide was placed in a semi-closed quartz boat in a static air environment and then calcined in a muffle furnace at 550°C for 4 h; next, the calcined material was ground into powder, rinsed with anhydrous ethanol and deionized water, collected by centrifugation, and dried in an oven at 60°C for 12 h to obtain bulk carbon nitride named CN. CN was dispersed in an open quartz boat and then calcined in a muffle furnace at 500°C for 4 h to obtain the final material named CN-T.

[0019] Example 1: Photocatalytic degradation of phenol wastewater and in-situ generation of H2O2 1. To verify the effect of phenol on the in-situ generation of H2O2, two experimental systems were set up: First, the photocatalytic reaction was carried out using a 21 W LED lamp with a maximum emission peak of 416 nm. The CN-T photocatalyst was added to deionized water with a dispersion concentration of 0.5 g / L. Secondly, in the first experimental system, deionized water was added to the beaker. In the second experimental system, phenol was added to the beaker until its concentration reached 40 mg / L. Finally, the resulting suspension was stirred in the dark for 30 min to allow the suspension to reach adsorption-desorption equilibrium, and then the light source was turned on for photocatalytic degradation. Every 30 min, 4 mL of the suspension was taken with a syringe and filtered through a 0.22 μm filter to analyze the phenol degradation efficiency and H2O2 production. Figure 1 It showed that only a trace amount of H2O2 was produced in deionized water. When phenol (40 mg / L) was present, we monitored that the H2O2 concentration showed a trend of first increasing and then decreasing. H2O2 reached its maximum concentration (about 790 μmol) after phenol was almost completely degraded.

[0020] 2. To verify the effect of phenol concentration on the in-situ generation of H2O2, the following experiment was set up: First, the photocatalytic reaction was carried out using a 21 W LED lamp with a maximum emission peak of 416 nm. The CN-T catalyst was added to deionized water with a dispersion concentration of 0.5 g / L; phenol was added to the beaker to a concentration of 10 mg / L, 20 mg / L, 30 mg / L, and 40 mg / L, respectively. Finally, the resulting suspension was stirred in the dark for 30 min to allow the suspension to reach adsorption-desorption equilibrium, and then the light source was turned on for photocatalytic degradation. Every 30 min, 4 mL of the suspension was taken with a syringe and filtered through a 0.22 μm filter to analyze the phenol degradation efficiency and H2O2 production.

[0021] Degradation rate Figure 2 As shown in a, a phenol solution with an initial concentration of 10 mg / L can be completely degraded after 60 min of illumination; the degradation rate of phenol solutions of 20 mg / L, 30 mg / L and 40 mg / L can also reach 100% after 120 min. With the increase of the initial concentration of phenol in the phenol-containing wastewater, the degradation rate of phenol by CN-T gradually decreased. At the same time, in the process of adding catalyst to degrade phenol, we monitored that the concentration of H2O2 showed a trend of first increasing and then decreasing. H2O2 usually reached its maximum concentration after phenol was almost completely degraded, and then decreased. According to Figure 2b. When the phenol concentration was 10 mg / L, the maximum concentration of H2O2 was about 250 μmol. When the phenol concentration increased to 40 mg / L, the maximum concentration of H2O2 reached about 790 μmol.

[0022] Example 2: Effect of phenol on aging of PE plastics 1. In order to verify the effect of phenol on aging of PE materials, two experimental systems were designed: First, the photocatalytic reaction was carried out using a 21 W LED lamp with a maximum emission peak of 416 nm. The CN-T catalyst was added to deionized water at a dispersion concentration of 0.5 g / L. A 2.5 cm × 2.5 cm plastic film was then added to the beaker. Deionized water or 40 mg / L phenol was then added to the beaker.

[0023] Secondly, in the first set of experimental systems, deionized water and PE plastic film were added to the beaker; in the second set of experimental systems, phenol was added to the beaker until its concentration reached 40 mg / L and PE plastic film.

[0024] Finally, the obtained suspension was stirred in the dark for 30 min to allow the suspension to reach adsorption-desorption equilibrium, and then the light source was turned on to carry out photocatalytic degradation reaction. The reaction time lasted for 48 h. During the plastic aging process, phenol solution of the initial concentration was added to the beaker every 3 h until the reaction was completed. Samples were taken during the reaction to detect the concentration of phenol. After the reaction, the plastic film was cleaned and dried for characterization.

[0025] Fourier transform infrared spectrometer was used to scan the original PE plastic, the PE plastic dried after reacting in deionized water for 48 h, and the PE plastic dried after reacting in phenol wastewater for 48 h. The scanning wavelength was 500~4000cm -1 , the results are shown in Figure 3 Compared with the original PE and the PE reacted in deionized water for 48 h, the infrared spectrum of the plastic reacted in phenol solution for 48 h showed three new peaks, namely OH (3278 cm -1 )、C=C(1633 cm -1 ) and CO (1205~1330 cm -1 ). These phenomena reflect that the H2O2 generated in situ by phenol wastewater can cause changes in the surface structure of PE plastic film, leading to its aging.

[0026] 2. To verify the effect of phenol concentration on plastic aging, the following experiment was conducted: First, the photocatalytic reaction was carried out using a 21 W LED lamp with a maximum emission peak of 416 nm. The CN-T catalyst was added to deionized water with a dispersion concentration of 0.5 g / L. Then a 2.5 cm×2.5 cm plastic film was added to the beaker. Phenol was then added to the beaker to concentrations of 10 mg / L, 20 mg / L, 30 mg / L, and 40 mg / L, respectively. The resulting suspension was stirred in the dark for 30 min to allow the suspension to reach adsorption-desorption equilibrium. Then the light source was turned on to carry out the photocatalytic degradation reaction. The reaction time lasted for 48 h. During the plastic aging process, the initial concentration of phenol solution was added to the beaker every 3 h until the reaction was completed. During the reaction, samples were taken to detect the concentration of phenol. After the reaction, the plastic films (named PE-10-48h, PE-20-48h, PE-30-48h, and PE-40-48h) were cleaned and dried for characterization.

[0027] Fourier transform infrared spectrometer was used to scan the PE plastics obtained by drying in the presence of different concentrations of phenol (10 mg / L, 20 mg / L, 30 mg / L, 40 mg / L) for 48 h at a scanning wavelength of 500-4000 cm -1 , the results are shown in Figure 4 a. When the phenol concentration was 40 mg / L, the in-situ generated H2O2 was the largest, and the carbonyl peak of PE after aging was the most obvious. When the phenol concentration was 10 mg / L, the in-situ generated H2O2 concentration was lower, 1637 cm -1 and 1205~1330 cm -1 The absorption peak in the region is not significant. Zoom in to 3100~3500 cm -1 In the hydroxyl region at 100 Å, a new broad peak was observed, indicating the presence of hydroxyl groups / hydroxyl peroxides. As the initial concentration of phenol increased, the concentration of H2O2 generated in situ increased further, and the migrated electrons reacted with the higher concentration of H2O2 to generate more •OH ( Figure 4 b) Used for aging PE.

[0028] Example 3: Effect of reaction time on plastic film aging In order to verify the effect of plastic film aging on reaction time, the following experiment was set up: First, the photocatalytic reaction was carried out using a 21 W LED lamp with a maximum emission peak of 416 nm. The CN-T catalyst was added to deionized water with a dispersion concentration of 0.5 g / L. Then a 2.5 cm×2.5 cm plastic film was added to the beaker. Deionized water or 40 mg / L phenol was added to the beaker. The resulting suspension was stirred in the dark for 30 min to allow the suspension to reach adsorption-desorption equilibrium. Then the light source was turned on to carry out the photocatalytic degradation reaction. The reaction time lasted for 12 h, 24 h, and 48 h, respectively. During the plastic aging process, the initial concentration of phenol solution was added to the beaker every 3 h until the reaction was completed. During the reaction, samples were taken to detect the concentration of phenol. After the reaction, the plastic films (named PE-40-12h, PE-40-24h, and PE-40-48h, respectively) were washed and dried for characterization.

[0029] Fourier transform infrared spectrometer was used to scan the polyethylene microplastics obtained by drying at different reaction times (12 h, 24 h, 48 h) at a phenol concentration of 40 mg / L, with a scanning wavelength of 500-4000 cm -1 , the results are shown in Figure 5 With the increase of irradiation time, the characteristic peak of C=O structure increases significantly, indicating that the aging degree of PE is positively correlated with the aging time.

Claims

1. A secondary thermally stripped C3N4 photocatalyst, characterized in that: The C3N4 photocatalyst is prepared by synthesizing bulk carbon nitride CN through thermal decomposition of dicyandiamide and then performing secondary calcination on the carbon nitride.

2. A secondary thermally stripped C3N4 photocatalyst as claimed in claim 1, characterized in that: The specific preparation method of the C3N4 photocatalyst is as follows: dicyandiamide is placed in a semi-closed quartz boat in a static air environment, and then calcined in a muffle furnace at 550°C for 4 hours; next, the calcined material is ground into powder, rinsed with anhydrous ethanol and deionized water, collected by centrifugation, and dried in an oven at 60°C for 12 hours to obtain a large piece of carbon nitride named CN; then CN is dispersed in an open quartz boat and calcined in a muffle furnace at 500°C for 4 hours to obtain a final material named CN-T, that is, the secondary thermally stripped C3N4 photocatalyst.

3. A method for accelerating the aging of microplastics by in-situ production of hydrogen peroxide using phenolic wastewater, characterized in that: In the wastewater to be treated in which phenolic pollutants and plastic films coexist, the secondary thermally stripped C3N4 photocatalyst described in claim 2 is added to form a photocatalytic degradation system, and H2O2 is generated in situ under light to achieve the coordinated photocatalytic degradation of phenolic pollutants and plastic films.

4. A method for accelerating the aging of microplastics by in-situ production of hydrogen peroxide from phenolic wastewater as claimed in claim 3, characterized in that: In the photocatalytic degradation system, the addition amount of the secondary thermally stripped C3N4 photocatalyst CN-T is 0.5 g / L, the concentration of the phenol pollutants is 0-40 mg / L, and no pH adjustment is required.

5. A method for accelerating the aging of microplastics by in-situ production of hydrogen peroxide from phenolic wastewater as claimed in claim 3, characterized in that: The phenolic pollutant is phenol, and the plastic film is a polyethylene plastic film.

6. A method for accelerating the aging of microplastics by in-situ production of hydrogen peroxide from phenolic wastewater as claimed in claim 5, characterized in that: The specific process is as follows: the concentration of phenolic pollutants in the wastewater to be treated containing plastic film is determined, and it is regulated by diluting or adding phenolic pollutants. During the plastic aging process, the initial concentration of phenol solution is added to the beaker every 3 hours until the reaction is completed, so that the concentration of phenolic wastewater is maintained at 10-40 mg / L; CN-T photocatalyst is added to the simulated wastewater to be treated in an amount of 0.5 g / L to form a C3N4 / LED photocatalytic degradation system; finally, magnetic stirring is performed at 500 rpm for 30 min under dark conditions, and then the photocatalytic degradation reaction is carried out under LED light for 12-48 hours, thereby completing the synergistic photocatalytic degradation of phenolic pollutants and plastic film.

Citation Information

Patent Citations

  • Method for promoting efficient photo-catalytic oxidation of phenolic pollutants by organic arsenic pollutants in situ

    CN110776079A